2003
DOI: 10.2527/2003.813587x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental nutrition around lambing on hair sheep ewes and lambs during the dry and wet seasons in the U.S. Virgin Islands1

Abstract: Pregnant St. Croix White and Barbados Blackbelly hair sheep ewes were used to evaluate the effect of supplemental nutrition around the time of lambing on ewe and lamb performance during the dry and wet seasons on St. Croix. Beginning 14 d before expected day of lambing (d 0) and for 21 d postpartum, one group of ewes was fed a pelleted supplement in addition to grazing guinea grass pasture (FEED). Other ewes in the flock grazed pasture only (CONTROL). This study was conducted during the dry season (June throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 6 publications
3
14
0
1
Order By: Relevance
“…Pérez-Hernández et al (2009) and Morales-Terán et al (2011) mention that females spending all day with their lambs tend to lose more weight than those who have controlled suckling, due to a greater synthesis of milk at the expense of their body reserves. Godfrey & Dodson (2003) mention that weight loss during lactation limits the reestablishment of cycling in females, which is why poor body condition prolongs the post-partum interval. Castillo-Maldonado et al (2013) report that in females whose nutritional requirements were covered, there were no significant differences between body weights in continuous and controlled suckling groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pérez-Hernández et al (2009) and Morales-Terán et al (2011) mention that females spending all day with their lambs tend to lose more weight than those who have controlled suckling, due to a greater synthesis of milk at the expense of their body reserves. Godfrey & Dodson (2003) mention that weight loss during lactation limits the reestablishment of cycling in females, which is why poor body condition prolongs the post-partum interval. Castillo-Maldonado et al (2013) report that in females whose nutritional requirements were covered, there were no significant differences between body weights in continuous and controlled suckling groups.…”
Section: Discussionmentioning
confidence: 99%
“…During summer, the shortest interval to estrus occurred when rainfall was greater than 200 mm, possibly being related to a better food quality. Godfrey and Dodson (2003) reported a shorter postpartum interval to estrus during the wet season, in which ewes received 10.1% CP food, than in the dry season (8.4% CP).…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that hair sheep can breed throughout the year at 17°N (Atti et al 2001;Wildeus 2005), although at latitudes higher than 25°, the incidence of estrus decreases during spring and increases again during late summer and autumn (Godfrey and Dodson 2003;Godfrey 2005;Wildeus 2005). According to individual differences in the reproductive activity throughout the year, some animals may still be sexually active during the otherwise conventional nonbreeding season.…”
Section: Introductionmentioning
confidence: 96%
“…This is in compliance with the results obtained by Son et al (1994), who reported similar live weight gain for ewes supplemented with 40 g or less of calcium salt protected fatty acids in post-lambig. However, Appeddu et al (2004) and Godfrey & Dodson (2003) found a decrease on ewes live weight supplemented with protected fat in comparison to the control diet.…”
Section: Resultsmentioning
confidence: 99%